Radiation effects on CMOS particle detectors - Debevc, Jernej (Matrika, 2021)
In particle physics experiments, silicon detectors usually constitute an essential part of the vertexing and tracking systems, situated closest to the interaction point. The products of particle collisions induce significant radiation damage in the detector material, which has to be well understood and accounted for to retain adequate performance throughout the detector lifetime. This article presents radiation damage in silicon and its effects on particle detectors, together with measurements of depletion properties of CMOS monolithic prototype detectors considered as an option for installation in the ATLAS Pixel Detector using the Edge-TCT technique.
Keywords: detektorji delcev; fizika osnovnih delcev; particle detectors; physics of elementary particles; silicijevi detektorji; silicon detectors